Comparative study of listing rules between stock exchanges. - Mok, Yonglin. (2008)
The aim of this study is to compare and analyze the features of listing rules under the Singapore Exchange (SGX), London Stock Exchange (LSE), New York Stock Exchange (NYSE) and Hong Kong Exchange (HKEx). This will assist a Singapore incorporated company in its choice for listing in a stock exchange.